2017
DOI: 10.1111/resp.13171
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of pleural infection: A complex warfare

Abstract: http://onlinelibrary.wiley.com/doi/10.1111/resp.13148/abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…In previous meta-analyses, it was concluded that there was equivocal evidence supporting the use of IPFT for these patients (8,9), with a more recent study unable to assess the impact of IPFT (10). Among factors contributing to the uncertainty, IPFT dosing remains empiric, and bioactivity of currently used IPFT agents was not confirmed in prior clinical trial testing in adults with empyema/CPE (19,20,25).…”
Section: Discussionmentioning
confidence: 99%
“…In previous meta-analyses, it was concluded that there was equivocal evidence supporting the use of IPFT for these patients (8,9), with a more recent study unable to assess the impact of IPFT (10). Among factors contributing to the uncertainty, IPFT dosing remains empiric, and bioactivity of currently used IPFT agents was not confirmed in prior clinical trial testing in adults with empyema/CPE (19,20,25).…”
Section: Discussionmentioning
confidence: 99%
“…PAI-1 neutralising antibodies have been shown to enhance the effectiveness of low doses of intrapleural fibrinolytic therapy [93]. This has paved the way for a single-chain urokinase plasminogen activator (scuPA), a fibrinolysin that is processed to a PAI-1 resistant form, and is currently in a phase 1 trial for patients with loculated pleural infections [94,95].…”
Section: The Effect Of Intrapleural Enzyme Therapy (Iet)mentioning
confidence: 99%
“…18 The pathobiology of pleural infection involves complex interplay between different cells of immunity, mediators of inflammation, the coagulation cascade and the offending organism(s), only a small part of which we understand thus far. 19 The pathophysiological model for pleural infection mainly describes the sequence of events from aspiration of oropharyngeal flora into lung parenchyma where infection ensues to invade the pleura space. These stages do not necessarily happen in primary pleural infection, where the organism spreads via the haematogenous route.…”
Section: Pathogenesismentioning
confidence: 99%